2019
DOI: 10.4081/ija.2019.1445
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the physiological and agronomic response of Armoracia rusticana grown in rainfed Mediterranean conditions

Abstract: Horseradish (Armoracia rusticana) is a perennial plant, belonging to the Brassicaceae family, whose roots are widely used as a cooking spice and flavouring agent across the world and has recently acquired considerable scientific interest due to the richness of phytochemicals. Aim of the study was to explore water relations in plants grown in pots and subject to severe stress conditions and gas exchange, plant growth, and agronomic characteristics of two horseradish accessions grown in open field under rainfed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is known that there is an interdependence between the content of phytoconstituents in horseradish and different abiotic factors (pH, humidity, temperature, light, etc.) [ 2 , 3 ]. Furthermore, various studies reported that the profiles of metabolites considered responsible for the aroma of horseradish differ, depending on the genotype and plant maturity [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that there is an interdependence between the content of phytoconstituents in horseradish and different abiotic factors (pH, humidity, temperature, light, etc.) [ 2 , 3 ]. Furthermore, various studies reported that the profiles of metabolites considered responsible for the aroma of horseradish differ, depending on the genotype and plant maturity [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 3 ]. Furthermore, various studies reported that the profiles of metabolites considered responsible for the aroma of horseradish differ, depending on the genotype and plant maturity [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%